Histone methyltransferase KMT2D sustains prostate carcinogenesis and metastasis via epigenetically activating LIFR and KLF4. Issue 10 (8th March 2018) - Lv, Shidong; Ji, Liyan; Chen, Bin; Liu, Shuqiang; Lei, Chengyong; Liu, Xi; Qi, Xiaoxiao; Wang, Ying; Lai-Han Leung, Elaine; Wang, Hongyi; Zhang, Lin; Yu, Xiaoming; et al.
Abstract Abnormalities in epigenetic modifiers are emerging as driving events in prostate cancer (PCa). The histone methyltransferase KMT2D, a frequently aberrant epigenetic modifier in various tumors, has an undefined role in PCa. Moreover, little is known regarding KMT2D's mutation in Chinese patients or its downstream signaling pathways and targets. Here, we profiled the mutational spectrum of 32 significantly PCa-associated genes by using disease-targeted sequencing, and found that KMT2D was highly mutated (63.04%, 29/46) in Chinese patients. Moreover, high KMT2D transcription was also associated with poor prognosis in an independent cohort (n = 51). In KMT2D-knockdown PC-3 and DU145 cells, cell proliferation (P < 0.01), invasion (P < 0.001), and migration (P < 0.01) were consequently suppressed. KMT2D depletion effectively suppressed tumor growth by 92.21% in vivo. Notably, integrative analyses of RNAseq and ChIPseq characterized two crucial genes downregulated by KMT2D, leukemia inhibitory factor receptor (LIFR) and Kruppel-like factor-4 (KLF4), which are regulators in PI3K/Akt and EMT, respectively. Our present study revealed that KMT2D epigenetically activates PI3K/Akt pathway and EMT by targeting LIFR and KLF4 and thus serves as a putative epigenetic-based target for treating PCa.